Underwater self-repairing high-tensile elastomer and preparation method thereof

By using composite materials of methyl methacrylate, ethyl acrylate and n-butyrate esterified ethyl cellulose, polymer network is formed, and the problem that self-healing materials cannot be efficiently self-healed in harsh underwater environments is solved, and the problem of self-healing materials cannot be efficiently self-healed in harsh underwater environments is achieved. Efficient self-healing and improvement of mechanical performance.

CN119390897AActive Publication Date: 2025-02-07NORTHEAST FORESTRY UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411601164.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Existing self-healing materials cannot be efficiently self-healed in harsh underwater environments, and it is difficult to maintain self-healing efficiency and elongation while enhancing the mechanical properties of the materials.

Method used

Using composite materials of methyl methacrylate, ethyl acrylate and n-butyrate esterified ethyl cellulose, a polymer network is formed through a photocuring process, using the rigid six-membered ring of ethyl cellulose to increase mechanical strength, and through the ester The modification prevents cellulose from self-aggregation, thereby maintaining self-healing ability and high tensile properties.

Benefits of technology

Efficient self-repair is achieved in various harsh underwater environments, while improving the mechanical properties of the material, maintaining self-repair efficiency and elongation, and the preparation method is simple and expandable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390897A_ABST
    Figure CN119390897A_ABST
Patent Text Reader

Abstract

The invention discloses an underwater self-repairing high-tensile elastomer and a preparation method thereof, and belongs to the field of elastomer preparation. The invention aims to solve the problems that an existing self-repairing material cannot realize efficient self-healing in a severe underwater environment, and the mechanical property of the material cannot be enhanced while the self-repairing efficiency and the tensile rate of the material cannot be maintained. The invention relates to an underwater self-repairing high-tensile elastomer, which is prepared from methyl methacrylate, ethyl acrylate and ethyl cellulose esterified by n-butyric acid. The method comprises the following steps: 1, preparing ethyl cellulose esterified by n-butyric acid; 2, mixing methyl methacrylate and ethyl acrylate; 3, adding ethyl cellulose subjected to n-butyric acid esterification and dissolving; and 4, ultraviolet curing. The invention is used for the underwater self-repairing high-tensile elastomer and the preparation thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of elastomer preparation. Background Art

[0002] Self-healing materials are a type of intelligent materials that can automatically repair their original properties after suffering external damage. Since the self-healing ability can effectively extend the service life of products and improve the reliability of materials, it has attracted widespread attention in the research community in the past few decades. Self-healing refers to the ability to self-repair when mechanically damaged. Self-healing materials repair cracks by changing chemical bonds or releasing and polymerizing self-healing monomers stored in the material, thereby maintaining the integrity of the matrix structure. Compared with traditional materials, self-healing materials have excellent performance and a wider range of use environments.

[0003] Considering the long-term use of self-healing polymers, high humidity conditions and even underwater conditions are inevitable. Therefore, the stability of self-healing polymers underwater has become one of the necessary properties. However, most of the existing reversible self-healing materials are not stable under harsh humid conditions because their reversible bonds have limitations in the self-healing process. Most of the current reversible self-healing materials are based on dynamic bonds, such as metal-ligand coordination, hydrogen bonds, ionic interactions, etc. Most of these dynamic bonds are unstable in water and are disturbed in many ways. Then the self-healing materials will swell and lose their self-healing ability. Therefore, it is still challenging to achieve self-healing under harsh conditions, such as underwater, seawater or strong acid / base conditions. At the same time, there is a restrictive relationship between self-healing and the strength and self-healing efficiency of the material. Generally, stronger physical cross-linking will provide harder and stronger material properties, but due to the presence of less rearranged networks on the damaged surface, the self-healing efficiency will be reduced, and the stretchability based on the nature of the material itself will also be restricted. In this conventional design, it is difficult to achieve a balance between the strength of the material and its self-healing efficiency and stretchability. Therefore, how to enhance the mechanical properties of the material with less loss of the material's self-healing efficiency and stretchability has always been a challenge and difficulty for self-healing materials. Summary of the invention

[0004] The present invention aims to solve the problem that existing self-repairing materials cannot self-heal efficiently in harsh underwater environments, and cannot maintain the self-repairing efficiency and stretchability of the materials while enhancing the mechanical properties of the materials, thereby providing a high-stretch elastomer that can self-heal underwater and a preparation method thereof.

[0005] A high tensile elastomer capable of underwater self-repairing is prepared from ethyl cellulose esterified with methyl methacrylate, ethyl acrylate and n-butyrate.

[0006] A method for preparing a high-strength elastomer capable of underwater self-repairing is carried out according to the following steps:

[0007] 1. Esterifying ethyl cellulose with n-butyric acid, and then drying to obtain n-butyric ethyl cellulose;

[0008] 2. mixing methyl methacrylate and ethyl acrylate uniformly to obtain a mixture A;

[0009] 3. adding n-butyrate-esterified ethyl cellulose to mixture A and dissolving it to obtain mixture B;

[0010] Fourth, the mixture B is UV-cured to complete the preparation method of the underwater self-repairable high-tensile elastomer.

[0011] The beneficial effects of the present invention are:

[0012] The present invention simultaneously utilizes the modification of plant fiber derivatives and the composite of ethyl acrylate and methyl methacrylate random copolymers, wherein after the ethyl cellulose is esterified with n-butyrate, it has good compatibility with ethyl acrylate and methyl methacrylate, effectively improving the mechanical properties of the polymer material, and maintaining the self-repairing efficiency and elongation of the material, thereby achieving efficient self-repairing in various harsh water environments.

[0013] The material is prepared by a photocuring process, through random copolymerization of hard segment methyl methacrylate (MMA) and soft segment ethyl acrylate (EA), and forms a polymer network with n-butyric ethyl cellulose (BEEC). The electronegative oxygen atoms on the ester group of the elastic material, the Debye force between the positive electrons and the carbon chain provide the healing ability of the material, wherein the Debye force has high density and excellent stability in a harsh water environment. In addition, the balance between mechanical strength and self-healing ability is related to the behavior of the polymer. Improving the mechanical strength of a single polymer material means increasing the interaction force between molecules, thereby causing the migration ability of the polymer chain to decrease. Therefore, the present invention utilizes the rigid six-membered ring of ethyl cellulose to increase the mechanical strength, and the natural structure of cellulose causes the mechanical strength of the composite material to increase significantly after adding a trace amount of ethyl cellulose. The esterification modification of ethyl cellulose can prevent cellulose from self-aggregating through hydrogen bonds, thereby providing a rigid skeleton for the material, and enhancing the interaction and miscibility between ethyl cellulose and polymer segments. The addition of BEEC also causes the polymer segments to stack loosely. This material forms a smaller domain, thereby ensuring the fluidity of the polymer segments. Therefore, it retains the self-healing ability and high tensile properties of the self-healing material. Since both the polymer chain and the modified ethyl cellulose have a hydrophobic structure and chemical inertness, the material is not affected by the harsh underwater environment and exhibits high self-healing ability in various harsh underwater environments.

[0014] The preparation method of the present invention is simple, and can be used to prepare large-sized materials. At the same time, the mechanical properties can be adjusted by changing the proportion of cellulose added. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The infrared spectra of the ethyl cellulose esterified with n-butyrate prepared in step 1 of the example and the ethyl acrylate described in step 2;

[0016] Figure 2 The ethyl cellulose prepared in step 1 of the embodiment is butyrated 1 H NMR spectra, 1 is ethyl cellulose, 2 is cellulose esterified with n-butyrate;

[0017] Figure 3 The figure is a comparison diagram of the mechanical tensile curves and elastic moduli of the elastomers prepared in Examples 1 to 2 and the comparative experiment, where a is the mechanical tensile curve and b is the elastic modulus;

[0018] Figure 4 The figure is a comparison of the mechanical tensile curve and self-repair efficiency of the underwater self-repairable high-stretch elastomer prepared in Example 1 after self-repair for 24 hours under different environments, where a is the mechanical tensile curve and b is the self-repair efficiency;

[0019] Figure 5 This is a comparison chart of the transmittance of the elastomers prepared in Example 1 and the comparative experiment, a is P(EA-co-MMA)-0, b is P(EA-co-MMA)-3; it can be seen from the figure that P(EA-co-MMA)-3 and P(EA-co-MMA)-0 have similar high transmittances above 80%;

[0020] Figure 6 These are SEM images of the elastomers prepared in Example 1 and the comparative experiment, a is P(EA-co-MMA)-0, b is P(EA-co-MMA)-3;

[0021] Figure 7 These are spectra of small angle scattering (SAXS) tests of the elastomers prepared in Example 1 and the comparative experiment, where a is P(EA-co-MMA)-0 and b is P(EA-co-MMA)-3. DETAILED DESCRIPTION

[0022] Specific implementation method 1: This implementation method is a high-stretch elastomer that can self-repair underwater, which is prepared from methyl methacrylate, ethyl acrylate and ethyl cellulose esterified with n-butyrate.

[0023] The beneficial effects of this embodiment are:

[0024] This embodiment simultaneously utilizes the modification of plant fiber derivatives and the composite of random copolymers of ethyl acrylate and methyl methacrylate, wherein after the ethyl cellulose is esterified with n-butyrate, it has good compatibility with ethyl acrylate and methyl methacrylate, effectively improving the mechanical properties of the polymer material, and maintaining the self-repair efficiency and elongation of the material, thereby achieving efficient self-repair in various harsh water environments.

[0025] The material is prepared by a photocuring process, through random copolymerization of hard segment methyl methacrylate (MMA) and soft segment ethyl acrylate (EA), and forms a polymer network with n-butyric ethyl cellulose (BEEC). The electronegative oxygen atoms on the ester group of the elastic material, the Debye force between the positive charge and the carbon chain provide the healing ability of the material, wherein the Debye force has high density and excellent stability in a harsh water environment. In addition, the balance between mechanical strength and self-healing ability is related to the behavior of the polymer. Improving the mechanical strength of a single polymer material means increasing the interaction force between molecules, thereby causing the migration ability of the polymer chain to decrease. Therefore, the present embodiment utilizes the rigid six-membered ring of ethyl cellulose to increase the mechanical strength, and the natural structure of cellulose causes the mechanical strength of the composite material to increase significantly after adding a trace amount of ethyl cellulose. The esterification modification of ethyl cellulose can prevent cellulose from self-aggregating through hydrogen bonds, thereby providing a rigid skeleton for the material, and enhancing the interaction and miscibility between ethyl cellulose and the polymer segment. The addition of BEEC also causes the polymer segment to pile up loosely. This material forms a smaller domain, thereby ensuring the fluidity of the polymer segment. Therefore, it retains the self-healing ability and high tensile properties of the self-healing material. Since both the polymer chain and the modified ethyl cellulose have a hydrophobic structure and chemical inertness, the material is not affected by the harsh underwater environment and exhibits high self-healing ability in various harsh underwater environments.

[0026] The preparation method according to the present embodiment is simple and can be used to prepare large-sized materials. At the same time, the mechanical properties can be adjusted by changing the proportion of cellulose added.

[0027] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the molar ratio of ethyl acrylate to methyl methacrylate is 1:(0.1-1). Other aspects are the same as specific embodiment 1.

[0028] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the mass ratio of the total volume of methyl methacrylate and ethyl acrylate to the n-butyrate ethyl cellulose is 10 mL: (0.1-0.5) g. The rest is the same as specific embodiment 1 or 2.

[0029] Specific embodiment 4: This embodiment is a method for preparing a high-strength elastic body capable of underwater self-repairing, which is carried out according to the following steps:

[0030] 1. Esterifying ethyl cellulose with n-butyric acid, and then drying to obtain n-butyric ethyl cellulose;

[0031] 2. mixing methyl methacrylate and ethyl acrylate uniformly to obtain a mixture A;

[0032] 3. adding n-butyrate-esterified ethyl cellulose to mixture A and dissolving it to obtain mixture B;

[0033] Fourth, the mixture B is UV-cured to complete the preparation method of the underwater self-repairable high-tensile elastomer.

[0034] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that: in step 1, the esterification reaction of ethyl cellulose with n-butyric acid is carried out according to the following steps: at room temperature, n-butyric acid and ethyl cellulose are mixed and reacted for 12h to 36h. The rest is the same as specific embodiment 4.

[0035] Specific embodiment 6: This embodiment is different from specific embodiment 4 or 5 in that the molar ratio of the n-butyric acid to the glucose unit of ethyl cellulose is 1:(0.1-1). The rest is the same as specific embodiment 4 or 5.

[0036] Specific embodiment 7: This embodiment is different from Specific embodiments 4 to 6 in that the molar ratio of ethyl acrylate to methyl methacrylate in step 2 is 1:(0.1-1). The rest is the same as Specific embodiments 4 to 6.

[0037] Specific embodiment 8: This embodiment differs from any one of specific embodiments 4 to 7 in that the mass ratio of the volume of the mixture A in step 3 to the n-butyrated ethyl cellulose is 10 mL: (0.1-0.5) g. The rest is the same as specific embodiments 4 to 7.

[0038] Specific embodiment 9: This embodiment is different from specific embodiments 4 to 8 in that the dissolution in step 3 is specifically performed at a temperature of 20° C. to 60° C. The rest is the same as specific embodiments 4 to 8.

[0039] Specific embodiment 10: This embodiment differs from specific embodiments 4 to 9 in that the UV curing described in step 4 is specifically performed at a wavelength of 265nm to 365nm and a power of 100w to 500w for 0.5h to 3h. The rest is the same as specific embodiments 4 to 9.

[0040] The following examples are used to verify the beneficial effects of the present invention:

[0041] Embodiment 1:

[0042] A method for preparing a high-strength elastomer capable of underwater self-repairing is carried out according to the following steps:

[0043] 1. At room temperature, n-butyric acid and ethyl cellulose are mixed and reacted for 24 hours, and then dried to obtain n-butyric ethyl cellulose;

[0044] The molar ratio of n-butyric acid to the glucose unit of ethyl cellulose is 1:1;

[0045] 2. mixing methyl methacrylate and ethyl acrylate uniformly to obtain a mixture A;

[0046] The molar ratio of ethyl acrylate to methyl methacrylate is 7:3;

[0047] 3. adding n-butyrate ethyl cellulose to mixture A and heating to dissolve the mixture at 50°C to obtain mixture B;

[0048] The mass ratio of the volume of the mixture A to the n-butyrated ethyl cellulose is 10 mL:0.3 g;

[0049] Fourth, the mixture B is added into the mold, and then UV-cured for 2 hours at a wavelength of 365nm and a power of 300W, and finally demolded to obtain a high-strength elastomer that can self-repair underwater.

[0050] Example 2: This example is different from Example 1 in that the mass ratio of the volume of the mixture A in step 3 to the n-butyrate ethyl cellulose is 10 mL:0.2 g. The rest is the same as Example 1.

[0051] Comparative experiment: The difference between this comparative experiment and Example 1 is that step 3 is omitted. The rest is the same as Example 1.

[0052] The names are given according to the amount of n-butyrated ethyl cellulose added. The tensile elastomer prepared in the comparative experiment is named P(EA-co-MMA)-0 (added amount 0 g), the high tensile elastomer capable of underwater self-healing prepared in Example 2 is named P(EA-co-MMA)-2 (added amount 0.2 g), and the high tensile elastomer capable of underwater self-healing prepared in Example 1 is named P(EA-co-MMA)-3 (added amount 0.3 g); n-butyrated ethyl cellulose is abbreviated as BEEC; ethyl acrylate is abbreviated as EA; and methyl methacrylate is abbreviated as MMA.

[0053] Figure 1This is the infrared spectrum of the butyrate-treated ethyl cellulose prepared in step 1 of the example and the ethyl acrylate described in step 2. As can be seen from the figure, ethyl cellulose has a rigid six-membered ring long-chain polysaccharide structure, and there are a large number of ester groups similar to ethyl acrylate on the surface of the modified ethyl cellulose.

[0054] Figure 2 The ethyl cellulose prepared in step 1 of the embodiment is butyrated 1 H NMR spectra, 1 is ethyl cellulose, 2 is cellulose esterified with n-butyrate; Figure 2 It was also verified that ethyl cellulose has a rigid six-membered ring long-chain polysaccharide structure, and the surface of the modified ethyl cellulose has a large number of ester groups similar to ethyl acrylate. This is the main reason why cellulose and elastomers can be miscible and maintain high healing ability. At the same time, it can be seen that the structure and composition of the composite material, the high content of ester groups inside the composite material is an important condition for cellulose to be uniformly compounded with polymer materials.

[0055] Mechanical testing was carried out at a test speed of 40 mm / min; Figure 3 The mechanical tensile curves and elastic modulus comparison diagrams of the elastomers prepared in Examples 1 to 2 and comparative experiments, a is the mechanical tensile curve, b is the elastic modulus; it can be seen from the figure that due to the homogeneous composite of cellulose and elastomer, the tensile properties of the composite material do not decrease with the increase of BEEC addition, and the mechanical properties are significantly improved. When BEEC is added to 0.3g / 10mL, its elastic modulus is 4 times higher than that of the pure self-healing matrix material, and the maximum tensile strength is doubled. The tensile strength of the underwater self-healing high-tensile elastomer prepared in Example 1 is 1.07MPa, the elastic modulus is 9.8±2.8MPa, and the elongation is 3689%.

[0056] The underwater self-healing high-strength elastomer prepared in Example 1 was cut into two parts, and then the two parts were gently re-contacted and placed in a dry environment or different water bodies. The two damaged cut surfaces healed spontaneously over time in different environments at room temperature. In the absence of any external stimulation, the self-healing efficiency is the ratio of the restored toughness to the original toughness (the area under the stress-strain curve, and the mechanical drop point is defined as the failure point due to the long stretching time). Figure 4This is a comparison diagram of the mechanical tensile curves and self-repair efficiency of the high-tensile elastomer capable of underwater self-repair prepared in Example 1 after self-repair for 24 hours in different environments, where a is the mechanical tensile curve and b is the self-repair efficiency. It can be seen from the figure that the self-healing efficiency is 92.3±9.5% in a dry environment for 24 hours; the self-healing efficiency is 91.2±6.1% in pure water for 24 hours; the self-healing efficiency is 87.4±8.8% in seawater (seawater samples are from the Bohai Sea in China) for 24 hours; the self-healing efficiency is 88.8±4.2% in physiological saline (concentration 0.9wt%) for 24 hours; the self-healing efficiency is 86.9±11.1% in NaOH with pH=13 for 24 hours; the self-healing efficiency is 82.8±2.4% in HCl with pH=1 for 24 hours.

[0057] The transmittance of 1.5 mm thick P(EA-co-MMA)-0 and P(EA-co-MMA)-3 was tested; Figure 5 The transmittance comparison diagram of the elastomer prepared in Example 1 and the comparative experiment, a is P(EA-co-MMA)-0, b is P(EA-co-MMA)-3; it can be seen from the figure that P(EA-co-MMA)-3 and P(EA-co-MMA)-0 have similar high transmittances of more than 80%; the composite material has a higher transmittance, the transmittance of 1.5mm thick P(EA-co-MMA)-0 is 86.5%, and the transmittance of P(EA-co-MMA)-3 is 87.0%. It can be seen that after adding BEEC, the transmittance does not decrease significantly, which is due to the good interface compatibility between the cellulose after n-butyrate esterification and the synthetic polymer elastomer substrate.

[0058] Figure 6 These are the SEM images of the elastomers prepared in Example 1 and the comparative experiment, a is P(EA-co-MMA)-0, b is P(EA-co-MMA)-3; SEM observation of the P(EA-co-MMA) surface shows that the surface of P(EA-co-MMA)-3 with cellulose modified with n-butyric acid is as flat as the surface of P(EA-co-MMA)-0, which indicates that the cellulose is uniformly dispersed inside the synthetic polymer elastomer.

[0059] Figure 7The spectra of the small angle scattering (SAXS) test of the elastomers prepared in Example 1 and the comparative experiment, a is P(EA-co-MMA)-0, b is P(EA-co-MMA)-3; by performing SAXS tests on P(EA-co-MMA)-0 and P(EA-co-MMA)-3, it can be found that the SAXS curve of P(EA-co-MMA)-0 has no obvious ordered peak, indicating that P(EA-co-MMA)-0 is a disordered structure. P(EA-co-MMA)-3 also has no obvious ordered peak, indicating that P(EA-co-MMA)-3 is also disordered. It was found that the addition of BEEC did not affect the microstructure of the P(EA-co-MMA)-0 composite material, and the composite material was still in a disordered state, which can effectively ensure the migration of molecular chains at room temperature, thereby ensuring the self-healing ability of the composite material at room temperature.

Claims

1. A high tensile elastomer capable of underwater self-repair, characterized in that It is prepared from ethyl cellulose esterified with methyl methacrylate, ethyl acrylate and n-butyrate.

2. The underwater self-repairable high-tensile elastomer according to claim 1, characterized in that The molar ratio of ethyl acrylate to methyl methacrylate is 1:(0.1-1).

3. The underwater self-repairable high-tensile elastomer according to claim 1, characterized in that The mass ratio of the total volume of the methyl methacrylate and ethyl acrylate to the n-butyrate-esterified ethyl cellulose is 10 mL: (0.1-0.5) g.

4. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 1, characterized in that It is carried out in the following steps:

1. Esterifying ethyl cellulose with n-butyric acid, and then drying to obtain n-butyric ethyl cellulose; 2. mixing methyl methacrylate and ethyl acrylate uniformly to obtain a mixture A; 3. adding n-butyrate-esterified ethyl cellulose to mixture A and dissolving it to obtain mixture B; Fourth, the mixture B is UV-cured to complete the preparation method of the underwater self-repairable high-tensile elastomer.

5. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 4, characterized in that In step 1, the esterification reaction of ethyl cellulose with n-butyric acid is specifically carried out according to the following steps: at room temperature, n-butyric acid and ethyl cellulose are mixed and reacted for 12 hours to 36 hours.

6. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 5, characterized in that The molar ratio of the n-butyric acid to the glucose unit of the ethyl cellulose is 1:(0.1-1).

7. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 4, characterized in that The molar ratio of ethyl acrylate to methyl methacrylate in step 2 is 1:(0.1-1).

8. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 4, characterized in that The mass ratio of the volume of the mixture A described in step 3 to the n-butyrated ethyl cellulose is 10 mL: (0.1-0.5) g.

9. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 4, characterized in that The dissolving in step 3 is specifically performed at a temperature of 20°C to 60°C.

10. The method for preparing a high tensile elastomer capable of underwater self-repairing according to claim 4, characterized in that The UV curing described in step 4 is specifically UV curing for 0.5h to 3h under the conditions of a wavelength of 265nm to 365nm and a power of 100w to 500w.

Citation Information

Patent Citations

  • Polyacrylate-nano cellulose composite slurry for foam starching and preparation method of polyacrylate-nano cellulose composite slurry

    CN104562671A

  • UV self-crosslinking polyacrylate and preparation method thereof

    CN107501463A

  • Modified ethyl cellulose polymer and preparation method thereof

    CN114957552A

  • Self-repairing polymer electrolyte and preparation method and application thereof

    CN118352647A

  • Resin composition including methacrylic based copolymer, molding and film

    JP2022102178A